1970
DOI: 10.1037/h0029265
|View full text |Cite
|
Sign up to set email alerts
|

Situational influences on the use of power.

Abstract: Kind of subordinate problem encountered and number of subordinates supervised were varied in an experimental study of the use of supervisory power The 5s were university students appointed to oversee the production of simulated workers. It was found that problems of discipline evoked Ss' use of coercive powers, while problems of ineptness evoked 5s use of expert powers Variations in the number of subordinates supervised influenced the amount of attention 5s could give to any one worker This resulted in less ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
68
0

Year Published

1977
1977
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(76 citation statements)
references
References 7 publications
8
68
0
Order By: Relevance
“…Judge and Ferris (1993) similarly suggested that the larger the span of control the less actual manager-follower contact occurs. Still other researchers (e.g., Cogliser & Schriesheim, 2000;Goodstadt & Kipnis, 1970;Green et al, 1996) proposed or found support for this contention. Time effects, however, have not been any more consistent regarding LMX than have studies of span of control.…”
Section: Individual Level: the Influence Of Span Of Control On Differmentioning
confidence: 94%
“…Judge and Ferris (1993) similarly suggested that the larger the span of control the less actual manager-follower contact occurs. Still other researchers (e.g., Cogliser & Schriesheim, 2000;Goodstadt & Kipnis, 1970;Green et al, 1996) proposed or found support for this contention. Time effects, however, have not been any more consistent regarding LMX than have studies of span of control.…”
Section: Individual Level: the Influence Of Span Of Control On Differmentioning
confidence: 94%
“…Our findings suggest that once a performance problem has been identified as a disciplinary issue, managerial decision processes often are not driven by a desire to "fit the punishment to the offense." Rather, decision makers appear to be influenced more by factors made important by norms relating to procedural fairness, to the accrual of rights through past contributions, and to the perceived need for authority (Goodstadt & Kipnis, 1970).…”
Section: Discussionmentioning
confidence: 99%
“…They also found that penalties were more severe for persons of lower organizational rank and for persons described as marginal (as opposed to «exceptional») in their talents, given the same infraction. Other research has shown that the emotional state of the supervisor and the manner of the subordinate (hostile or uncooperative) moderate the intensity of the discipline applied (Goodstadt and Kipnis, 1970;Kipnis, Silverman and Copeland, 1973). Evidence from a study by Shaak and Schwartz (1973) indicated that managers at higher organizational levels recommended more severe penalties for a set of hypothetical offences than did managers at lower levels.…”
Section: This Study Is Directed To the Issue Ofwhat Détermines The Immentioning
confidence: 99%